Salmonella Typhi From Blood Cultures in the Democratic Republic of the Congo: A 10-Year Surveillance. (7th March 2019) - Tack, Bieke; Phoba, Marie-France; Van Puyvelde, Sandra; Kalonji, Lisette M; Hardy, Liselotte; Barbé, Barbara; Van der Sande, Marianne A B; Monsieurs, Elise; Deborggraeve, Stijn; Lunguya, Octavie; Jacobs, Jan
Abstract: Background: This study gives an overview of a decade (2007–2017) of hospital-based Salmonella Typhi bloodstream infection (BSI) surveillance in the Democratic Republic of the Congo (DRC), at 4 main sampling sites. Methods: Blood cultures were sampled in hospital-admitted patients with suspected BSI, according to standardized clinical indications. The results of the surveillance period 2015–2017 were compiled with those of previous surveillance periods (2007–2010 and 2011–2014). Whole genome sequencing of isolates with decreased ciprofloxacin susceptibility (DCS) was performed. Results: Salmonella Typhi was isolated in 1.4% (531/37 388) and 10.3% (531/5177) of suspected and culture-confirmed BSI episodes, respectively. Salmonella Typhi ranked first among the BSI pathogens in adults (n = 220), but was mostly (n = 301 [56.7%]) isolated from children, of which 72.1% (217/301) and 31.6% (95/301) were <10 years and <5 years old, respectively. Multidrug resistance (MDR), DCS, and combined MDR/DCS were found in 38.3% (n = 180), 24.5% (n = 115), and 11.9% (n = 56) of 470 first isolates, respectively. MDR and DCS rates had increased since 2007, but remained stable during 2015–2017 with no geographical clustering at the province level. Most (91/93 [97.8%]) DCS isolates sequenced belonged to Genotyphi genotype 2.5.1, and gyr S83 was the most frequent DCS mutation (76/93 [81.7%]). Infections occurred perennially, but increased during the rainy season. Conclusions: Salmonella Typhi was a frequent cause of BSI in adults and children in DRC, with high rates of antibiotic resistance. Sustainable surveillance and implementation of vaccination are compelling.